Presentation and Endoscopic Findings of Emergency Upper Gastrointestinal Bleeding: A Seven-Year Experience at King Abdulaziz University Hospital, Jeddah, Saudi Arabia - Abdul Rahman M. Sibiany (Journal of King Abdulaziz University: Medical Sciences, 2023)
Emergency upper gastrointestinal bleeding is a major cause of morbidity and mortality. Internationally, the three most common causes are peptic ulcer disease, erosive gastritis and esophageal varies. This is a seven-year retrospective analysis of the presentations and endoscopic diagnoses of patients admitted to King Abdulaziz University Hospital with emergency upper gastrointestinal bleeding. A total of 1149 patients were included, the majority were males (76.5%). Most patients (82.6%) had hematemesis, while 14.5% had melena; the remaining had both. Bleeding esophageal varies was the most common cause (37.6%), followed by peptic ulcer disease (23.7%) and gastritis (11.3%). Portal hypertension was found to be a major risk factor as Saudi Arabia is endemic for chronic Hepatitis B and C, with a high prevalence of intestinal schistosomiasis. Emergency upper gastrointestinal endoscopy is effective for diagnostic and therapeutic purposes. Those findings were compatible with the results published by other local authors, although 61.4% of our patients were non-Saudis.